2016
DOI: 10.1038/srep37810
|View full text |Cite|
|
Sign up to set email alerts
|

Impairment of PDGF-induced chemotaxis by extracellular α-synuclein through selective inhibition of Rac1 activation

Abstract: Parkinson’s disease (PD) is characterized by α-synuclein (α-Syn)-positive intracytoplasmic inclusions, known as Lewy bodies. Although it is known that extracellular α-Syn is detected in the plasma and cerebrospinal fluid, its physiological significance remains unclear. Here, we show that extracellular α-Syn suppresses platelet-derived growth factor (PDGF)-induced chemotaxis in human neuroblastoma SH-SY5Y cells. The inhibitory effect was stronger in the mutant α-Syn(A53T), found in hereditary PD, and the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
(37 reference statements)
3
12
0
Order By: Relevance
“…4, hatched green bars in the raft fractions), indicating gangliosides as a receptor or binding partner of ␣-Syn(A53T) to elicit pathophysiological responses including expulsion of S1P 1 R from the raft fractions. Consistent with this notion, an ␣-Syn mutant devoid of ganglioside-binding ability, ␣-Syn(K34A/Y39A/K45A)-derived (32) mutant, ␣-Syn(A53T/ K34A/Y39A/K45A), and ␣-Syn(A53T)-AAA (27), lost the capacity to expel S1P 1 R from the lipid rafts ( Fig. 4).…”
Section: Role Of Gangliosides For Extracellular Action Of ␣-Synsupporting
confidence: 60%
See 2 more Smart Citations
“…4, hatched green bars in the raft fractions), indicating gangliosides as a receptor or binding partner of ␣-Syn(A53T) to elicit pathophysiological responses including expulsion of S1P 1 R from the raft fractions. Consistent with this notion, an ␣-Syn mutant devoid of ganglioside-binding ability, ␣-Syn(K34A/Y39A/K45A)-derived (32) mutant, ␣-Syn(A53T/ K34A/Y39A/K45A), and ␣-Syn(A53T)-AAA (27), lost the capacity to expel S1P 1 R from the lipid rafts ( Fig. 4).…”
Section: Role Of Gangliosides For Extracellular Action Of ␣-Synsupporting
confidence: 60%
“…Growing lines of evidence support that ␣-Syn has an intrinsic property to interact with gangliosides: interaction of GM1 with Extracellular ␣-Syn drives S1P 1 receptor out of lipid rafts ␣-Syn, and inhibition of its fibrillation (31) or contrary to this, acceleration of ␣-Syn aggregation with vesicles containing GM1 or GM3 (34), determination of ganglioside-binding specificity of ␣-Syn showing the importance of tyrosine 39 residue of the protein (32), and importance of GM1 for the internalization of extracellular ␣-Syn in microglia (35). A recent report (27) from our laboratory has shown that extracellular ␣-Syn causes impairment of PDGF-induced chemotaxis through selective inhibition of Rac1 activation. Subsequently, after dissection of the signaling pathway upstream of the Rac1 activation, we have revealed that extracellular ␣-Syn induces S1P 1 R uncoupled from G i (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-SYN overexpression in model systems, and its concomitant aggregation and deposition precede neuronal cell death. In the case of DAn, its degeneration is influenced by intracellular and extracellular α-SYN accumulation, mainly in its oligomeric form [ 70 ] . Interestingly, extracellular oligomeric α-SYN impairs RAC1 activity in neuroblastoma cells [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported from this laboratory that extracellular α-Syn inhibits PDGF-induced chemotaxis19. To identify signalling pathway, which is important in PDGF-induced chemotaxis and that is sensitive to extracellular α-Syn, we first examined the involvement of S1P signalling in this phenomenon.…”
Section: Resultsmentioning
confidence: 99%